Factors that impact the level of acceptance of end-user on using epayment system in Malaysia - Lee, Feng Ming (2022)
This research paper aims to examine the Factors that impact the level of acceptance of end-user on using E-payment system in Malaysia. This research paper has determined the relationship between the independent variables and dependent variable and also explains the dependent variable and each independent variable by reviewing previous research literature. The independent variables are Perceived Ease of Use, Trust, Benefit and Self-efficacy and the dependent variable is Intention of end-user using E-payment. This research paper aims to examine the Factors that impact the level of acceptance of end-user on using E-payment system in Malaysia. This research paper has determined the relationship between the independent variables and dependent variable and also explains the dependent variable and each independent variable by reviewing previous research literature. The independent variables are Perceived Ease of Use, Trust, Benefit and Self-efficacy and the dependent variable is Intention of end-user using E-payment. In this research questionnaires and secondary data are based on journals and online databases were used to collect data. For the respondents are e-payment end-users in Malaysia. A total of 120 sets of questionnaires were successfully collected. The results for descriptive analysis, reliability test, and inferential analysis were obtained through the IBM SPSS software. After the analysis, the result shows that all the independent variables have a positive relationship with intention of end-user using E-payment and Benefit has the strongest relationship with intention of end-user using E-payment. Lastly, the limitations encountered and the recommendations for future studies have been discussed in the last chapter of this research.